2015
DOI: 10.1039/c5ta07223a
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional hard carbon matrix for sodium-ion battery anode with superior-rate performance and ultralong cycle life

Abstract: A three-dimensional (3D) hard carbon matrix (3DHCM) derived from sodium polyacrylate precursor was achieved, delivering a superior-rate performance and ultralong cycle life performance, and a sodium-ion full cell property 39x37mm (600 x 600 DPI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(43 citation statements)
references
References 50 publications
2
39
0
Order By: Relevance
“…For example, the sodium-ion full-cell system coupling layer-structured transition metal oxide cathodes and hard carbon anodes has experienced great progress in recent several years, as shown in Figure 5. [73,[132][133][134][135][136][137][138][139][140][141][142][143][144][145][146][147][148] Komaba et al reported a hard carbon//NaNi 1/2 Mn 1/2 O 2 full cell, which has an operating voltage of 3 V at the 1 C rate and an estimated specific energy density of 60% of the current state-of-the-art graphite//LiCoO 2 system. [138] As shown in Figure 5a over 200 cycles at the 0.5 C rate.…”
Section: Asymmetric Sodium-ion Full-cell System With Carbonaceous Anodementioning
confidence: 99%
“…For example, the sodium-ion full-cell system coupling layer-structured transition metal oxide cathodes and hard carbon anodes has experienced great progress in recent several years, as shown in Figure 5. [73,[132][133][134][135][136][137][138][139][140][141][142][143][144][145][146][147][148] Komaba et al reported a hard carbon//NaNi 1/2 Mn 1/2 O 2 full cell, which has an operating voltage of 3 V at the 1 C rate and an estimated specific energy density of 60% of the current state-of-the-art graphite//LiCoO 2 system. [138] As shown in Figure 5a over 200 cycles at the 0.5 C rate.…”
Section: Asymmetric Sodium-ion Full-cell System With Carbonaceous Anodementioning
confidence: 99%
“…12). In this section, we systematically review those anode materials and analyse their sodium storage mechanisms [121].…”
Section: Anode Materials For Sodium-ion Batteriesmentioning
confidence: 99%
“…To improve the energy density of Na 3 V 2 (PO 4 ) 3 ‐based full cells, a hard‐carbon anode with high specific capacity and low average voltage has also been applied. It, however, fails to realize high energy density due to large polarization . In order to solve this problem, Mai's group proposed a polarization suppresssion strategy to improve the output voltage of the full cell.…”
Section: Non‐aqueous Cathode‐based Sifcsmentioning
confidence: 99%